Digital Brand Storytelling: A Strategic Tool for Enhancing Consumer Brand Relationships - Fahrurozi; Yuli (Trasearch (Training, Research and Academy Society, 2025)
In an era where digital interactions dominate consumer-brand engagement, storytelling has emerged as a vital strategy for brands seeking to cultivate emotional and lasting relationships. Despite increasing investments in digital content, many brands struggle to authentically connect with consumers, often due to a lack of narrative coherence and emotional depth. This study addresses the critical question of how digital brand storytelling influences consumer-brand relationships by applying a grounded theory approach. The research aims to explore the mechanisms through which narrative elements shape consumers’ perceptions, trust, and loyalty toward a brand in digital environments. Utilizing in-depth interviews with marketing professionals and digital consumers, the study identifies key themes such as authenticity, relatability, narrative coherence, and value alignment. The results demonstrate that when executed with emotional resonance and cultural sensitivity, storytelling significantly enhances consumer trust, brand identification, and engagement. This finding confirms that storytelling is not merely a creative tactic but a strategic relational tool. The study offers practical insights for marketers to shift from product-centric messages to human-centric narratives that reflect consumer values and lived experiences. Theoretically, it expands existing brand communication models by integrating narrative theory into digital brand relationship frameworks. These insights suggest that brand storytelling, when grounded in authenticity and emotional meaning, can serve as a long-term relational asset in the digital economy.